EFEKTIVITAS METODE PEMBELAJARAN DARING (DALAM JARINGAN) PADA MATA KULIAH ASUHAN KEBIDANAN - Husna Farianti Amran; Linda Suryani (LPPM Universitas Abdurrab, 2021)
The Covid-19 pandemic has had an impact on the world of education. To prevent the spread of COVID-19, the government issued a policy to close all educational institutions. Learning activities are carried out by Distance Learning or called online learning. This requires the ability of lecturers and students to be able to use information technology effectively so that learning objectives can be achieved. This study aims to determine the effectiveness of online learning methods on student learning outcomes. This type of research is quantitative with an analytic design with a coss sectional approach. The population of all students of the program study S1 Midwifery STIKes Payung Negeri Pekanbaru, which amounted to 36 people, the entire population was used as the object of research. The study was conducted in March–June 2021. Data were collected using a questionnaire and analyzed by univariate and bivariate. The results obtained that the effectiveness of online learning methods is in the effective category 58.3% (21 respondents), the aspect of the effectiveness of online learning methods is the use of appropriate media 72.3% (26 respondents), student learning outcomes are in the Good category 58, 3% (21 respondents) and there is a relationship between the effectiveness of online learning methods and student learning outcomes (r= 0.509) with a moderate level t = 3.448. It is expected that lecturers as educators can pay attention to aspects such as: using appropriate learning media, good instructional strategies, varied learning activities, and extensive learning resources, so that online learning can be carried out effectively. and learning objectives can be achieved which can be seen from good student learning outcomes